Preparation method of Cs2AgBiBr6 / Bi2WO6 composite material and application of Cs2AgBiBr6 / Bi2WO6 composite material in selective photocatalytic ammoxidation of aromatic hydrocarbon

By using CS2AGBIBR6/BI2WO6 composite material for photocatalytic catalytic, the lack of high temperature, high pressure and complex catalysts in the existing toluene ammonia oxidation process achieved low -cost, low -temperature and high -efficiency ammonia oxidation reactions.

CN119327491APending Publication Date: 2025-01-21SUZHOU INST FOR ADVANCED STUDY USTC +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411458860.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing toluene oxidation process requires high temperature, high pressure and complex catalysts, which are costly and harsh, making it difficult to achieve efficient and low-cost reactions.

Method used

The Cs2AgBiBr6/Bi2WO6 composite material was prepared by precipitation method and mechanical ball milling method, and was used to photocatalyze the ammonia oxidation of methylarenes, which simplified the synthesis process and improved the catalytic efficiency.

Benefits of technology

Ammoxidation of methylaromatic hydrocarbons is achieved at low temperature (around 120°C), low pressure, and solvent-free conditions, with high selectivity and efficient photocatalytic performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119327491A_ABST
    Figure CN119327491A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a Cs2AgBiBr6 / Bi2WO6 composite material, which comprises the following steps: respectively preparing Cs2AgBiBr6 powder and Bi2WO6 powder, and then mechanically grinding the Cs2AgBiBr6 powder and the Bi2WO6 powder. The invention also discloses a corresponding composite material and application of the composite material in selective photocatalytic ammoxidation of methyl aromatic hydrocarbon. The surface of the composite material is rough, a large number of active sites can be provided, adsorption of reactants on the surface of a catalyst is enhanced, proceeding of a photochemical reaction is facilitated, electron separation and transfer between crystals are promoted through a load structure, and liquid-phase toluene ammoxidation can be efficiently photo-catalyzed into benzonitrile under visible light.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method of a Cs2AgBiBr6 / Bi2WO6 composite material and application of the composite material in selective photocatalytic aromatic hydrocarbon ammoxidation, belonging to the technical field of photocatalytic preparation of chemicals. Background Art

[0002] Bismuth-based catalysts are typical semiconductor photocatalysts and have attracted widespread attention in recent years due to their unique band structure and high physical and chemical stability. The halide double perovskite Cs2AgBiBr6 has a long carrier lifetime, effective carrier mass and mobility. Bi2WO6 has attracted much attention due to its high stability, non-toxicity and low cost. Patent document CN 116459848A published a composite material of bismuth-based perovskite Cs3Bi2Br9 and Bi2WO6 for the oxidation of benzyl alcohol. [1] However, the synthesis method of the material is different from that described in this article, and the absorption range of Cs3Bi2Br9 is narrow, and the visible light range that can be used is relatively small. There are also literatures that have published composite materials of Cs2AgBiBr6 and Bi2WO6 for photocatalytic CO2 reduction. [2-4] and photocatalytic degradation of pollutants [5] , but the synthesis methods are different from this paper: References [2-4] need to use hot injection to synthesize Cs2AgBiBr6 quantum dots for compounding with Bi2WO6, and the hot injection method is complicated and difficult to scale up; the Cs2AgBiBr6 in reference [5] needs to be synthesized in a glove box (oxygen-free environment), and their synthesis methods are more complicated. In comparison, the precipitation method for synthesizing Cs2AgBiBr6 and the mechanical ball milling method for synthesizing composite materials provided in this paper are simpler and easier to repeat.

[0003] Toluene ammoxidation is a complex process. The C(sp3)-H of toluene has high energy, is difficult to break, and is not easy to react. Therefore, existing toluene ammoxidation processes use high-cost and harsh conditions such as high temperature (280℃-450℃), high pressure, and complex catalysts. [6-7] Photocatalysis can be considered as one of the cleanest synthetic routes, and using photocatalysis to improve the reaction conditions of toluene ammoxidation is a promising application direction.

[0004] [1] A benzyl alcohol oxidation semiconductor photocatalyst and its preparation method and application CN 116459848A.

[0005] [2]Wang H,Wang X,Hu P,et al.Vacancy pair induced surface chemistryreconstruction of Cs2AgBiBr6 / Bi2WO6 heterojunction to enhance photocatalyticCO2 reduction[J].Applied Catalysis B:Environment and Energy,2024,351123956-.

[0006] [3]Lijun Wu,Song Zheng,Heng Lin,et al.In-situ assembling 0D / 2D Z-scheme heter ojunction of Lead-free Cs2AgBiBr6 / Bi2WO6 for enhancedphotocatalytic CO2 reduction[J].Colloid Interface Sci.2023Jan;629(Pt A):233-242.

[0007] [4]Jiaqi Wang,Hao Cheng,Dingqiong Wei,et al.Ultrasonic-assistedfabrication of Cs2AgBiBr6 / Bi2WO6 S-scheme heterojunction for photocatalytic CO2reduction under visible light[J].Chinese Journal of Catalysis.2022,43(10):Pages 2606-2614

[0008] [5]Hailin Z,Xu J,Haiyang X,et al.Halide double perovskites Bi2WO6 / Cs2AgBiBr6 with efficient charge separation and wide visible light absorptionfor high activity photocatalysis[J].Journal of Alloys and Compounds,2023,968.

[0009] [6] Teimouri A, Najari B, Chermahini NA, et al. Characterization and catalytic properties of molybdenum oxide catalysts supported on ZrO2–γ-Al2O3 for ammoxidation of toluene[J]. RSC Advances, 2014, 4(71): 37679-37686.

[0010] [7][1]Shubhra SA, Shilpi G, Rubina K, et al. Unravelling the role of Ag-Cr interfacial synergistic effect in Ag / Cr2O3 nanostructured catalyst for theammoxidation of toluene via low temperature activation of Csp 3 -H bond[J].Catalysis Communications,2021,152 Summary of the invention

[0011] The purpose of the present invention is to provide a method for preparing a Cs2AgBiBr6 / Bi2WO6 composite material. The prepared Cs2AgBiBr6 / Bi2WO6 composite material can be applied to selective photocatalytic methyl aromatic ammoxidation.

[0012] The technical solution adopted by the present invention is:

[0013] A method for preparing a Cs2AgBiBr6 / Bi2WO6 composite material, comprising the steps of:

[0014] (1) CsBr, AgBr and BiBr3 are dissolved in DMSO at a molar ratio of 2:1:1 to form a Cs2AgBiBr6 / DMSO precursor solution, the precursor solution is dropped into isopropanol, the precipitated solid is washed with isopropanol, and dried to obtain Cs2AgBiBr6 powder;

[0015] (2) Bi(NO3)3·5H2O and Na2WO4·2H2O were dissolved in ethylene glycol at a molar ratio of 2:1, the resulting solution was transferred to a hydrothermal reactor, heated for a period of time, and dried to obtain Bi2WO6 powder;

[0016] (3) Cs2AgBiBr6 powder and Bi2WO6 powder are mixed in proportion, and a Cs2AgBiBr6 / Bi2WO6 composite material is obtained by mechanical grinding and drying, wherein the proportion of Cs2AgBiBr6 is 10-40wt%.

[0017] Preferably, the heating reaction temperature in step (2) is 160° C. and the time is 18-24 hours.

[0018] Preferably, after the heating reaction in step (2) is completed, the reaction product is washed alternately with deionized water and ethanol and then dried.

[0019] Preferably, the mechanical grinding time in step (3) is more than 20 minutes.

[0020] The present invention also discloses a Cs2AgBiBr6 / Bi2WO6 composite material, which is composited from Cs2AgBiBr6 powder and Bi2WO6 powder, wherein the proportion of Cs2AgBiBr6 is 10-40wt%.

[0021] Application of the above-mentioned Cs2AgBiBr6 / Bi2WO6 composite material in selective photocatalytic methyl aromatic ammoxidation.

[0022] Application of the above-mentioned Cs2AgBiBr6 / Bi2WO6 composite material in the photocatalytic preparation of aromatic nitrile from methyl aromatic hydrocarbons.

[0023] Preferably, methyl aromatic hydrocarbon and Cs2AgBiBr6 / Bi2WO6 composite material are added to the reactor, and then the reactor is sealed and filled with ammonia oxygen mixed gas, heated and exposed to light for reaction to generate aromatic nitrile. The reaction formula is shown below:

[0024]

[0025] Wherein R is H, F, Cl, Br, CH3, CF3, tert-butyl, etc.

[0026] Preferably, the total pressure of the ammonia-oxygen mixed gas is 1-5 bar, the ammonia ratio is 20-80%, it is heated to 100-130° C., and the wavelength range of the light source is 365-450 nm.

[0027] The more preferred reaction conditions are adding 50 mg of 20 wt% Cs2AgBiBr6 / Bi2WO6 per 5 ml of substrate, a total pressure of 5 bar (40% O2+60% NH3), 120°C, and 450 nm. At this time, the yield of photocatalytic conversion of toluene to benzonitrile is 86.5 μmol, and the selectivity is 78%.

[0028] The beneficial effects of the present invention are as follows:

[0029] (1) The Cs2AgBiBr6 / Bi2WO6 composite material provided by the present invention has a rough surface, which can provide a large number of active sites, enhance the adsorption of reactants on the catalyst surface, and is more conducive to the photochemical reaction. In addition, the loading structure promotes the separation and transfer of electrons between crystals.

[0030] (2) The preparation method of the Cs2AgBiBr6 / Bi2WO6 composite material provided by the present invention has simple raw materials, simple operation, and is easy to repeat. It not only has low energy consumption but is also simple and efficient.

[0031] (3) The Cs2AgBiBr6 / Bi2WO6 composite material provided by the present invention can be used for the photocatalytic ammoxidation of methyl aromatics, which greatly improves the ammoxidation conditions of methyl aromatics, allowing the reaction to be carried out at low temperature (about 120°C) and low pressure in the absence of solvent, and has high selectivity for aromatic nitriles.

[0032] In summary, the composite material enhances light absorption capacity, promotes electron separation and transfer, and improves photocatalytic performance, and can efficiently photocatalyze liquid-phase toluene ammoxidation to benzonitrile under visible light. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is the XRD spectrum of the Cs2AgBiBr6 / Bi2WO6 composite material prepared in Example 1.

[0034] Figure 2 This is a transmission electron microscope image of the Cs2AgBiBr6 / Bi2WO6 composite material prepared in Example 1.

[0035] Figure 3 This is a comparison chart of the toluene ammonia oxidation performance of Cs2AgBiBr6 / Bi2WO6 composite materials made from Bi2WO6 synthesized under different conditions.

[0036] Figure 4 This is a comparison chart of the photocatalytic toluene ammonia oxidation performance of pure Bi2WO6 and Cs2AgBiBr6 / Bi2WO6 composites with different loading amounts under visible light.

[0037] Figure 5 This is the GC-MS graph of the product obtained in Example 2 under the catalytic action of the composite material with a loading rate of 20%. DETAILED DESCRIPTION

[0038] The present invention is further illustrated by examples below, but is not intended to be limiting of the present invention. The specific materials used in the embodiments of the present invention and their sources are provided below. However, it should be understood that these are merely exemplary and are not intended to limit the present invention, and materials identical or similar to the types, models, qualities, properties or functions of the following reagents and instruments can be used to implement the present invention. The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial sources.

[0039] Example 1. Preparation of Cs2AgBiBr6 / Bi2WO6 composite material

[0040] The specific steps are as follows:

[0041] (1) CsBr (4 mmol), AgBr (2 mmol) and BiBr3 (2 mmol) were dissolved in 10 mL DMSO to form a DMSO precursor solution, the precursor solution was dropped into isopropanol, the precipitated solid was washed with isopropanol, and dried to obtain Cs2AgBiBr6 powder;

[0042] Those skilled in the art can understand that as long as the molar ratio of CsBr, AgBr and BiBr3 is controlled to be 2:1:1, and the added CsBr, AgBr and BiBr3 are ensured to be soluble in DMSO, the added amounts of CsBr, AgBr and BiBr3 in DMSO can be changed, and the Cs2AgBiBr6 powder required by the present invention can also be obtained;

[0043] (2) Dissolve Bi(NO3)3·5H2O (2 mmol) and Na2WO4·2H2O (1 mmol) in 15-30 mL of ethylene glycol, transfer the resulting solution into a 50 mL Teflon-lined hydrothermal reactor, heat to 160°C and maintain for 18-24 h, wash with deionized water and ethanol alternately, and dry to obtain Bi2WO6 powder;

[0044] (3) Mix a certain proportion of Cs2AgBiBr6 and Bi2WO6 solid powders, and mechanically grind them to make Cs2AgBiBr6 and Bi2WO6 nanoparticles composite. Generally, the grinding time is more than 20 minutes to make the powders evenly mixed, and obtain Cs2AgBiBr6 / Bi2WO6 composite materials. The proportion of Cs2AgBiBr6 is controlled at 10-40wt%. The size of the composite nanoparticles is 100-200nm. The XRD spectrum is shown in Figure 1As shown, the diffraction peaks were compared with the standard peaks on the standard Bi2WO6 PDF card one by one, and it was found that the peak positions and peak intensities were completely combined. After compounding with Cs2AgBiBr6, the characteristic peaks of Cs2AgBiBr6 appeared, and the peaks of Cs2AgBiBr6 were higher as the loading amount increased. The transmission electron microscopy image of the Cs2AgBiBr6 / Bi2WO6 composite material with a loading rate of 20% is shown in Figure 2 As shown, most of the particles are distributed in the range of 100-200 nm, mixed with a small amount of small particles smaller than 100 nm.

[0045] Example 2: Toluene ammoxidation performance test

[0046] 5 mL of toluene and 50 mg of catalyst sample were added to the reactor, and then the reactor was sealed and filled with oxygen and ammonia (ammonia accounted for 20%-80%) (total pressure was 1-5 bar), heated to 120°C, and started to irradiate with light (410-500 nm). The reaction was terminated after 15 hours of continuous reaction. The reaction formula is as follows. GC-MS was used to detect the product in the reaction solution. The GC-MS graph is as follows: Figure 5 shown.

[0047]

[0048] When 50mg 20wt% Cs2AgBiBr6 / Bi2WO6 (Bi2WO6 synthesis conditions are 30ml ethylene glycol, 160℃ for 24h) is used as catalyst, total pressure is 5bar (40% O2+60% NH3), 120℃, and light source wavelength is 450nm, the yield of photocatalytic conversion of toluene into benzonitrile is 86.5μmol, and the selectivity is 78%. When other conditions remain unchanged, the yield of benzonitrile is 87μmol at a total pressure of 1bar, and the selectivity is 75%. When other conditions remain unchanged, the yield of benzonitrile is 127μmol at 5bar (20% NH3), and the selectivity is 77%; when other conditions remain unchanged, the yield of benzonitrile is 84μmol at 5bar (80% NH3), and the selectivity is 78%. When other conditions remain unchanged, the yield of benzonitrile is 129 μmol and the selectivity is 74% when the wavelength of the light source is 410 nm; when the wavelength of the light source is 500 nm, the yield of benzonitrile is 37 μmol and the selectivity is 32.2%; when the wavelength of the light source is 365 nm, the yield is 160 μmol and the selectivity is 68%. When other conditions remain unchanged, the yield is 48 μmol and the selectivity is 75% when the reaction temperature is adjusted to 100°C; when the temperature is 130°C, the yield is 120 μmol and the selectivity is 72%.

[0049] The amount of ethylene glycol used and the heating holding time in the process of synthesizing Bi2WO6 in Example 1 were changed, and the obtained Bi2WO6 was mixed with Cs2AgBiBr6 under the same conditions to obtain 20wt% Cs2AgBiBr6 / Bi2WO6, and the reaction was carried out under the conditions of total pressure of 5bar (40% O2+60% NH3), 120°C, 450nm, and 15h. The relationship between the product and the amount of ethylene glycol used and the heating holding time is as follows: Figure 3 As shown in Figure 2, it can be seen that the catalytic performance of Bi2WO6 under different synthesis conditions is not much different.

[0050] Other conditions remain unchanged, using 50 mg Bi2WO6 or Cs2AgBiBr6 / Bi2WO6 with different Cs2AgBiBr6 contents as catalyst, the relationship between the obtained product and the catalyst is as follows Figure 4 As shown, it can be seen that the composite Cs2AgBiBr6 / Bi2WO6 material can significantly improve the selectivity and catalytic efficiency of the reaction.

[0051] Example 3: Performance test of trifluoromethyltoluene ammoxidation

[0052] Add 5 mL of trifluoromethyltoluene and 50 mg of catalyst sample into the reactor, then seal the reactor and fill it with oxygen and ammonia (ammonia accounts for 20%-80%) (total pressure is 1-5 bar), heat to 120°C, start illumination (410-500 nm, 60 mW / cm2), and terminate the reaction after 15 hours of continuous reaction. The reaction equation is as follows. Use GC-MS to detect the product in the reaction solution.

[0053]

[0054] 50mg 20wt% Cs2AgBiBr6 / Bi2WO6 (Bi2WO6 synthesis conditions are 30ml ethylene glycol, 160℃ for 24h), total pressure 5bar (40% O2+60% NH3), 120℃, light source wavelength 450nm, the photocatalytic conversion of trifluoromethyltoluene into trifluoromethylbenzonitrile has a yield of 52μmol and a selectivity of 78%.

[0055] The substrate can also be replaced by other methyl aromatic compounds. The Cs2AgBiBr6 / Bi2WO6 composite material also has the function of catalyzing the ammoxidation of other methyl aromatic compounds, and has high selectivity for conversion into aromatic nitriles.

Claims

1. A method for preparing a Cs2AgBiBr6 / Bi2WO6 composite material, characterized in that The steps include: (1) CsBr, AgBr and BiBr3 are dissolved in DMSO at a molar ratio of 2:1:1 to form a Cs2AgBiBr6 / DMSO precursor solution, the precursor solution is dropped into isopropanol, the precipitated solid is washed with isopropanol, and dried to obtain Cs2AgBiBr6 powder; (2) Bi(NO3)3·5H2O and Na2WO4·2H2O were dissolved in ethylene glycol at a molar ratio of 2:1, the resulting solution was transferred to a hydrothermal reactor, heated for a period of time, and dried to obtain Bi2WO6 powder; (3) Cs2AgBiBr6 powder and Bi2WO6 powder are mixed in proportion, and a Cs2AgBiBr6 / Bi2WO6 composite material is obtained by mechanical grinding and drying, wherein the proportion of Cs2AgBiBr6 is 10-40wt%.

2. The preparation method according to claim 1, characterized in that: The heating reaction temperature in step (2) is 160° C. and the time is 18-24 hours.

3. The preparation method according to claim 1, characterized in that: After the heating reaction in step (2) is completed, the reaction product is washed alternately with deionized water and ethanol and then dried.

4. The preparation method according to claim 1, characterized in that: The mechanical grinding time in step (3) is more than 20 minutes.

5. A Cs2AgBiBr6 / Bi2WO6 composite material, characterized in that It is composited by Cs2AgBiBr6 powder and Bi2WO6 powder, wherein Cs2AgBiBr6 accounts for 10-40wt%.

6. Use of the Cs2AgBiBr6 / Bi2WO6 composite material according to claim 5 in selective photocatalytic ammoxidation of methyl aromatic hydrocarbons.

7. Use of the Cs2AgBiBr6 / Bi2WO6 composite material according to claim 5 in the photocatalytic preparation of aromatic nitrile from methyl aromatic hydrocarbons.

8. The use according to claim 7, characterized in that: Methyl aromatic hydrocarbons and Cs2AgBiBr6 / Bi2WO6 composite materials are added into the reactor, which is then sealed and filled with ammonia-oxygen mixed gas, heated and illuminated for reaction to generate aromatic nitrile.

9. The use according to claim 8, characterized in that: The total pressure of the ammonia-oxygen mixed gas is 1-5 bar, the ammonia ratio is 20-80%, it is heated to 100-130° C., and the wavelength range of the light source is 365-450 nm.

Citation Information

Patent Citations

  • Benzyl alcohol oxidation semiconductor photocatalyst as well as preparation method and application thereof

    CN116459848A